2017
DOI: 10.1097/lgt.0000000000000277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Viral Load as a Triage Strategy With Primary High-Risk Human Papillomavirus Cervical Cancer Screening

Abstract: Human papillomavirus viral load level is positively associated with cervical lesion grade. Ten relative light units/control or greater is a viable threshold for immediate colposcopy whereas 1 or greater or less than 10 RLU/CO is advised to reflex cytology for optimizing sensitivity and specificity, as well as referral rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 25 publications
5
30
0
1
Order By: Relevance
“…However, this association lost significance when other cofactors were considered in multivariate analysis. This study showed high consistency with previous studies using Hybrid Capture II assay detecting a pool of 13 HR-HPV types for a association between the viral burden of HPV and cervical lesions [7,[20][21]. Nonetheless, the present study indicates that histological severity of cervical lesions is not an independent factor for HR-HPV load, and its effect is not obvious when other cofactors are taken into consideration.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, this association lost significance when other cofactors were considered in multivariate analysis. This study showed high consistency with previous studies using Hybrid Capture II assay detecting a pool of 13 HR-HPV types for a association between the viral burden of HPV and cervical lesions [7,[20][21]. Nonetheless, the present study indicates that histological severity of cervical lesions is not an independent factor for HR-HPV load, and its effect is not obvious when other cofactors are taken into consideration.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, the present study indicates that histological severity of cervical lesions is not an independent factor for HR-HPV load, and its effect is not obvious when other cofactors are taken into consideration. Association between HPV viral load and cervical lesions is complex [6][7][8]. High viral load has an elevated likelihood of having cells with transforming infections and viral integration into the cellular genome [17,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berggrund et al [14] showed that the HR-HPV viral load could indicate the course of the infection, as well as the presence of CIN II, CIN III, and CC. A previous study also showed a correlation between the HC2 viral load and CIN grade [34]. Nevertheless, a study suggested that a single measure of HOV viral load could not reliably indicate the presence of CIN [35].…”
Section: Discussionmentioning
confidence: 89%
“…However, the relation between HR-HPV viral load and future risk of HSIL or CC is less certain. Many studies have reported that viral load increases with the elevation of disease severity [6,7], while others have not con rmed such an increased risk of disease progression [8].…”
Section: Introductionmentioning
confidence: 99%